Littering for $500: How Does Judicial Estoppel Solve the Problems that Factually Baseless Pleas Pose to the Double Jeopardy Clause? - Rob Mangone (Washington University Law Review, 2020)
A factually baseless plea is one entered by a defendant for an offense that the defense, prosecution, and judge know that the defendant did not commit. Factually baseless pleas undermine justice. Inherently, these pleas are lies that our system has adopted to patch together a case-by-case attempt to render fair verdicts. While these factually baseless pleas may help individual defendants receive lenient sentences and may allow prosecutors and judges to quickly clear their caseloads, they do not provide a consistent and predictable criminal legal system. These pleas undermine the intent of the legislature because the crimes that the legislature defined are no longer being enforced. When a prosecutor amends a crime to a lesser included or related crime, the crime still has some factual basis that ensures the defendant is being “appropriately” punished for his or her actions. However, when the defendant accepts a factually baseless plea, his or her punishment is only related to the crime by the prosecutor’s loose approximation of what justice requires. This is an inappropriate way to determine justice. This Note advocates for the use of judicial estoppel to protect criminal defendants from subsequent prosecutions after they accept a factually baseless plea. While the elimination of factually baseless pleas would be preferable to the “band-aid” solution that judicial estoppel presents, the lack of actors calling for the elimination of factually baseless pleas makes their abolition in the near future unlikely. In the meantime, judicial estoppel would prevent prosecutors from abusing factually baseless pleas, ensure that the courts do not expose defendants to multiple punishments for the same offense, and safeguard the integrity of the court system.
Keywords: Factually baseless pleas; Judicial estoppel; Criminal law; Legislative intent; Double jeopardy; Fifth amendment; Plea bargains